Theoretical aerodynamics - Milne-Thomson, L. M. 1891-1974 (Dover Publications, 1973)
An excellent introduction to the study of inviscid airflow using potential theory, this book is a longtime university text and reference and a classic in its field. This edition is a complete reprint of the revised 1966 edition, which brings the subject up to date. Includes a wealth of problems, illustrations, and cross-references.